2022
DOI: 10.25271/sjuoz.2022.10.3.924
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Sludge in Zakho Municipal Wastewater by Anaerobic Digestion for Biogas Production in Kurdistan Region, Iraq

Abstract: Raw wastewater sludge samples were collected from two sanitary point sources in Zakho city wastewater pipes. Anaerobic digestion is utilized sludge stabilization as it was effective in reducing the volume of sludge and cheap source of clean biogas. the sludge of municipal wastewater of Zakho district is worth to be used for the generation of biogas and just 15 -17 kg sludge produced 233 to 350 m3 gas in solid retention time of 18 and 24 day respectively. Suspended solid is close related to the amount of COD th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Digesters were carried out at a sludge retention time (SRT) of 15 days with the mesophilic temperature of 30 ± 0.5 • C. SRT is important for the anaerobic digestion of POME WAS as it serves the purpose of ensuring that sufficient time was given for hydrolysis to take place [30]. A typical mesophilic digester requires a SRT range of 15 to 30 days for better solids minimization [31]. However, it is important to take into account that a prolonged SRT would lead to the bulking of inert compounds that would slow down the microbial activity, while a short SRT would cause the washing out of methanogens [32].…”
Section: Anaerobic Digestion (Ad)mentioning
confidence: 99%
“…Digesters were carried out at a sludge retention time (SRT) of 15 days with the mesophilic temperature of 30 ± 0.5 • C. SRT is important for the anaerobic digestion of POME WAS as it serves the purpose of ensuring that sufficient time was given for hydrolysis to take place [30]. A typical mesophilic digester requires a SRT range of 15 to 30 days for better solids minimization [31]. However, it is important to take into account that a prolonged SRT would lead to the bulking of inert compounds that would slow down the microbial activity, while a short SRT would cause the washing out of methanogens [32].…”
Section: Anaerobic Digestion (Ad)mentioning
confidence: 99%
“…The municipal waste water in Iraqi Kurdistan region suffer from proper sanitary sewer system and produce sewage sludge contain high amounts of pollutant as they accumulated over long time without removal and treatments [22]. The biological oxygen demand (BOD) is crucial for heterotrophic aerobic microbial population in order to break down the organic waste for carbon and energy source.…”
Section: Wastewater Physiochemical Properties Improved By Primary Tre...mentioning
confidence: 99%
“…This hurts aquatic ecosystems. [9] reported that the Zakho city releases huge amounts of non-treated sewage sludge in the Khabur river and the sludge produced is worth to be utilized as a cheap source for producing biogas by anaerobic stabilization. The physic-chemical properties of rivers are varied among seasons as in winter more silt and trash are carried with flood water and deposited in rivers, as well as these characteristics are affected by the watersheds that feed the rivers and the spatial location of rivers, especially passing pass through big cities that release many pollutants in rivers [10].…”
Section: Introductionmentioning
confidence: 99%